Mobility and Handover Management in 5G/6G Networks: Challenges, Innovations, and Sustainable Solutions - Bilal Saoud; Ibraheem Shayea; Mohammad Ahmed Alnakhli; Hafizal Mohamad (MDPI AG, 2026)
Tier 1- Indexed by WOS/SCOPUS/ERA